Gastrointestinal Bleeding Secondary to Portal Hypertensive Duodenopathy in a Patient with Decompensated Liver Cirrhosis - Rohini Krishna; Samuel O. Igbinedion; Richie Diaz; Nazneen Hussain; Moheb Boktor (Case Reports in Gastrointestinal Medicine)
With alcoholic cirrhosis and nonalcoholic fatty liver disease continuously on the rise in the United States, there is also a corresponding rise in portal hypertension. Portal hypertensive duodenopathy (PHD) is a complication of portal hypertension not commonly seen in cirrhotic patients. We present a case of a 46-year-old man who presented with decompensated liver cirrhosis secondary to gastrointestinal bleed. The patient underwent esophagogastroduodenoscopy (EGD) with findings indicative of PHD. Patient subsequently underwent transjugular intrahepatic portosystemic shunt (TIPS) with resolution of gastrointestinal bleed. We highlight TIPS as a management strategy in patients with PHD for whom less invasive measures are not effective.